Unit Knowledge and Practice of Emergency Nursing Interventions at a Tertiary Public Cardiac Health Center in Uganda - Namukwaya, Harriet; Aliga, Cliff Asher; Nakate, Grace; Mutyabule, Judith (International Journal of Critical Care, 2022)
Research suggests that many of the millions of deaths and long-term disabilities resulting from acute cardiovascular events and other emergency conditions are preventable if effective emergency care services were readily available. Effective emergency care requires trained and competent staff, including registered nurses. Most educational pathways do not adequately prepare nurses to deliver sensitive health care services for those with acute illness and injury. This includes Uganda, where few capacity-building initiatives have targeted emergency nursing care delivery, leading to knowledge and practice gaps. This study aimed to assess emergency nursing knowledge and clinical practice at a tertiary public cardiac health facility in Uganda. This was a single-center, descriptive cross-sectional survey of a convenience sample of nurses working in the emergency department. A total of 49 emergency care nurses completed the survey (response rate of 81.6%). Among the participants, 75.5% were females, 65.3% had a bachelor's degree, 28.6% had Basic Life Support training, and 12.2% were certified in Advanced Cardiac Life Support. Additionally, 75% of the respondents had low proficiency in assessing critically ill patients, 100% could not perform safety checks, 50% could not maintain patent airways or complete patient handover, and only 50% could connect a patient to a defibrillator. We report that the most significant gap in nurse-provided emergency care is the application of practical skills. Capacity-building initiatives are required to improve the knowledge and practice of nurses in emergency care delivery.